Aging mechanism of microplastics with UV irradiation and its effects on the adsorption of heavy metals - Mao, Ruofan; Lang, Mengfan; Yu, Xiaoqin; Wu, Renren; Yang, Xiaomei; Guo, Xuetao (Journal of hazardous materials, 2020)
[Display omitted] •PS were aged by air, pure water and seawater under UV irradiation.•Changes in chemical/physical properties of PS were examined by FTIR, XPS, XRD and SEM.•Aging mechanisms of PS in water environment is different from that in air.•Aging can significantly improve the adsorption of heavy metals by PS. Microplastics are formed by the degradation of plastic wastes under the action of physicochemical mechanisms in environment, and they are becoming a new type of pollutant that is attractings global attention. However, research on the aging characteristics and mechanism of microplastics is limited. The aging mechanism of Polystyrene (PS) with UV irradiation under different conditions (air, pure water and seawater) and the effect of aging on heavy metal adsorption were studied. The results show that PS have different characteristics with UV irradiation under different conditions, and the aging of PS is the most obvious in air. Based on the 2D-COS analysis, different aging mechanisms were identified under different aging conditions, aging sequence of aged PS functional groups in air and water were clearly definited. An isothermal adsorption model shows that aging can significantly increase the adsorption of heavy metals by PS. The adsorption of heavy metals is also affected by different aging methods. Over all, a 2D-COS analysis was an effective method for understanding the aging process of PS. These results further clarify the aging mechanism of PS, and provides a theoretical basis for the assessment of environmental behavior and ecological risk when microplastics and heavy metals coexist.